PENGARUH IKLIM PSIKOLOGIS DAN BUDAYA ORGANISASI, TERHADAP KEPUASAN KERJA KARYAWAN DAN OCB DI UD. SEKAR JAGAT - Anata, Putu Yoga; Suwandana, I Gusti Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2019)
Organizational Citizenship Behavior is a behavior that is not part of an employee's formal work obligations but supports the functioning of the organization effectively. The purpose of this study was to determine the effect of Psychological Climate, Organizational Culture, and Job Satisfaction on Organizational Citizenship Behavior at UD Sekar Jagat, Denpasar, Bali using saturated sample technique or census. The data collected in this study were analyzed using path analysis. The results showed that the psychological climate and organizational culture had a positive and significant effect on job satisfaction. Second, the psychological climate and organizational culture have a positive and significant effect on organizational citizenship behavior. Third, job satisfaction has a positive and significant effect on organizational citizenship behavior. The implication that can occur from this research is that companies must create a psychological climate and good organizational culture.